2013
DOI: 10.1180/claymin.2013.048.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical investigations of the first package of the alternative buffer material test – I. Alteration of bentonites

Abstract: Bentonite, which is envisaged as a promising engineered barrier material for the safe disposal of highly radioactive waste, was and is investigated in different large scale tests. The main focus was and is on the stability (or durability) of the bentonite. However, most countries concentrated on one or a few different bentonites only, regardless of the fact that bentonite performance in different applications is highly variable. Therefore, SKB (Svensk Kärnbränslehantering) set up the first large scale test whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 9 publications
2
28
1
Order By: Relevance
“…With regard to the distribution of exchangeable cations, the lateral gradient was basically insignificant, except for Mg 2+ concentrations in samples nearest to the steel heater. A small decrease occurred within 20 mm of the interface in the present study, although the increase in Mg at the contact was reported in the bentonites used in the ABM test packages (Kaufhold et al, 2013;Kumpulainen et al, 2016). No significant change was observed for the sum of exchangeable cations (total cations) within the JNB01 sample.…”
Section: Chemical Propertiescontrasting
confidence: 72%
See 2 more Smart Citations
“…With regard to the distribution of exchangeable cations, the lateral gradient was basically insignificant, except for Mg 2+ concentrations in samples nearest to the steel heater. A small decrease occurred within 20 mm of the interface in the present study, although the increase in Mg at the contact was reported in the bentonites used in the ABM test packages (Kaufhold et al, 2013;Kumpulainen et al, 2016). No significant change was observed for the sum of exchangeable cations (total cations) within the JNB01 sample.…”
Section: Chemical Propertiescontrasting
confidence: 72%
“…Unlike the XRD results with humidity control, the EPMA results do not support an Fe 2+ -for-Na + exchange by smectite near the I-B interface. An alternative reason for the Fe enrichment observed at this location might involve the precipitation of Fe(III) oxyhydroxides (Ishidera et al, 2008;Wersin et al, 2015) and/or the formation of siderite (Kaufhold et al, 2013;Wersin et al, 2015) resulting from the corrosion of the steel. Enrichment of Ca and Fe near the I-B interface may also be due to the precipitation of carbonate; thus the siderite formation should not be ignored.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Ca-rich bentonites do not tend to release colloidal particles as Na-bentonites do. Furthermore, the larger selectivity of Ca(Mg) towards the interlayer and the fact that most host-rock waters do contain some Ca will cause fast cation exchange if Na-bentonites are contacted with such solutions (Kaufhold et al, 2013;Dohrmann et al, 2013b). A general recommendation of the type of exchangeable cation initially present may be redundant because of the fast equilibration of the bentonite with the surrounding water.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…This model, therefore, will be further improved. 4) Kaufhold et al (2013) investigated one block of each different clay material used in the first package of the Ä spö hard rock laboratory ABM-test (alternative buffer material test). They found the different materials to have reacted differently and finally summarized all alteration mechanisms as FeÀ, C org , C inorg , SO 4 -accumulation and mineral dissolution.…”
Section: (Received 12 April 2013)mentioning
confidence: 99%